Everyone a Changemaker? Exploring the Moral Underpinnings of Social Innovation Discourse Through Real Utopias - Teasdale, Simon; Roy, Michael J.; Ziegler, Rafael; Mauksch, Stefanie; Dey, Pascal; Raufflet, Emmanuel B. (Journal of Social Entrepreneurship, 2021)
The term ‘social innovation’ has come to gather all manner of meanings from policymakers and politicians across the political spectrum. But while actors may unproblematically unite around a broad perspective of social innovation as bringing about (positive) social change, we rarely see evidence of a shared vision for the kind of social change that social innovation ought to bring about. Taking inspiration from methods that recognise the utopian thinking inherent in the social innovation concept, we draw upon Erik Olin Wright’s concept of ‘real utopias’ to investigate the moral underpinnings inherent in the public statements of Ashoka, one of the most prominent social innovation actors operating in the world today. We seek to animate discussion on the moral principles that guide social innovation discourse through examining the problems that Ashoka is trying to solve through social innovation, the world they are striving to create, and the strategies they propose to realise their vision.
Publisher: Routledge _eprint: https://doi.org/10.1080/19420676.2020.1738532
Keywords: Changement; Innovation sociale; Utopie